Distress disclosure on social media and depressive symptoms among college students: the roles of social comparison and gender - Ye, Xiaoli; Gao, Haohao (Frontiers in Psychology, 2025)
IntroductionIn contemporary society, individuals are commonly exposed to multiple pressures, under which emotional disorders occur frequently. Especially the upward trend of depressive symptoms among the young population constitutes a non-negligible public health challenge. As social media is increasingly integrated into daily life, individuals’ emotional experiences strongly connect with online interactions. Thus, it is essential to investigate the relationship between the social media usage behavior of young people and their mental health conditions.MethodsThis study conducted an online survey involving 405 college students using the DDI (Distress Disclosure Index), INCOM (Iowa-Netherlands Comparison Orientation Measure), and CES-D (Center for Epidemiologic Studies Depression Scale). It employed a moderated mediation model to explore the connection between distress disclosure on social media and depressive symptoms and the potential roles of social comparison and gender.ResultsThe results indicate the following: (1) Distress disclosure on social media is associated with depressive symptoms; (2) Social comparison mediates the relationship between distress disclosure on social media and depressive symptoms among college students; (3) Gender moderates the effect of distress disclosure on social media regarding social comparison, with a more pronounced moderation effect observed in male participants.DiscussionThe findings of this study underscores the importance of adopting appropriate strategies for disclosing distress, fostering healthy tendencies toward social comparison, and recognizing gender differences in mitigating depressive symptoms among young adults.